Athlete Branding = Atlet Markalaşması - Van Schaik, Thomas (Eastern Mediterranean University, Social Media Unit, 2016)
Thomas van Schaik (@thomasvanschaik) Thomas van Schaik has over 20 years of global strategic marketing, social media and public relations expertise in sports, sponsorship, media and business, producing award winning and cutting-edge programs designed to increase ROI and minimize cost. He has worked with confederations, organizing committees, leagues and teams from around the world and with many of today's best athletes; ranging from Super Bowl winners and NBA All Stars to World- and Olympic Champions. He's currently authoring a book on 'Athlete Branding and how todays athletes engage their fans and build their brands'. Thomas has been connected to the Dutch Olympic Committee & Dutch Sports (NOC*NSF) since September 2015. As Marketing & Commerce Director he's currently responsible for strengthening its innovative brand and sponsorship programs. Prior to his time at NOC*NSF Thomas' worked in the NFL Europe, with football club PSV Eindhoven and in a variety of global roles at sporting goods manufacturer Adidas. Athlete Branding: "When people become brands" Athletes come in all shapes and sizes. So do their personal brands; from hometown hero to global icon. Sure; people are all still people, but athletes and artists have become the most visible examples of the human side of branding. Since the beginning of time athletes have fascinated and inspired their audience. Today, globalization and socialization are rapidly changing the impact, influence and income of athletes. Fans are driven by an emotional connection to their favorite athlete through deep seated personal motivators. Winning isn't everything. Fans are driven by purpose. Sports fans, just like fans of any brand, don't see themselves so much as buying products, but rather belonging to a larger movement. In this presentation we will review how today's athletes engage their fans and build their brands.
Eastern Mediterranean University, Social Media Unit, in collaboration with EMU Communication and Media Studies Faculty, is organising a “Social Media and Brand Week” between 6 and 7 April 2016.
Keywords: Athlete Marketing; Social Media; Athletes - Brands